2019
DOI: 10.1091/mbc.e18-01-0047
|View full text |Cite
|
Sign up to set email alerts
|

The roles of a flagellar HSP40 ensuring rhythmic beating

Abstract: HSP40s are regarded as cochaperones, perpetually shuttling client polypeptides to HSP70s for refolding. However, many HSP40s that are central for disparate processes diverge from this paradigm. To elucidate the noncanonical mechanisms, we investigated HSP40 in the radial spoke (RS) complex in flagella. Disruption of the gene by the MRC1 transposon in Chlamydomonas resulted in jerky flagella. Traditional electron microscopy, cryo-electron tomography, and sub-tomogram analysis revealed RSs of various altered mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…Ciliary motility is an ATP-dependent process that results in activation of dynein motor proteins between the pairs of microtubule doublets that are the major structural component of the ciliary axoneme ( Satir and Sleigh, 1990 ). A number of studies indicate that signals from the central pair propagate through radial spokes to modulate the dynein activity and, ultimately, affect ciliary beating and flagellar movement ( Adams et al, 1981 ; Smith and Yang, 2004 ; Wirschell et al, 2009 ; Yang and Smith, 2009 ; Zhu et al, 2019 ). These studies generally conclude that dynein is a downstream effector of the central pair apparatus ( Huang et al, 1982 ; Porter et al, 1994 , 1992 ; Rupp et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ciliary motility is an ATP-dependent process that results in activation of dynein motor proteins between the pairs of microtubule doublets that are the major structural component of the ciliary axoneme ( Satir and Sleigh, 1990 ). A number of studies indicate that signals from the central pair propagate through radial spokes to modulate the dynein activity and, ultimately, affect ciliary beating and flagellar movement ( Adams et al, 1981 ; Smith and Yang, 2004 ; Wirschell et al, 2009 ; Yang and Smith, 2009 ; Zhu et al, 2019 ). These studies generally conclude that dynein is a downstream effector of the central pair apparatus ( Huang et al, 1982 ; Porter et al, 1994 , 1992 ; Rupp et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the structures of radial spokes in the axonemal unit, especially those of RS1 and RS2, seem to be very similar, several studies have indicated that there are some differences in their protein composition. Depletion of RSP16/HSP40 (heat shock protein) in Chlamydomonas alters the structure of the neck and head of both RS1 and RS2, but to different extents [141]. In the ciliate Tetrahymena , knocking out FAP206, an evolutionarily conserved protein, results in the lack of RS2 (and rarely RS3 as well), while RS1 is unaffected.…”
Section: Radial Spokesmentioning
confidence: 99%
“…Chlamydomonas cells with mutations in genes encoding the RSP3 protein, an ortholog of RSPH3, lack the entire RS1 and RS2 and have paralyzed flagella, while the flagella assembled by the RSP4 mutants (Chlamydomonas RSP4 is an ortholog of human RSPH4A) lack only the radial spokes' head and move abnormally [195,196]. The depletion of the HSP40/DNAJ13B in Chlamydomonas causes minor structural defects in the neck of RS1 and RS2, but these two complexes are affected to a different extent [197]. Flagella of the mutated cells move in an uncoordinated way, generally without cells propelling [198].…”
Section: Radial Spokesmentioning
confidence: 99%
“…Flagella of the mutated cells move in an uncoordinated way, generally without cells propelling [198]. It was proposed that HSP40, besides its function as a chaperone, stabilizes the distal part of the docked radial spokes [197].…”
Section: Radial Spokesmentioning
confidence: 99%